Symphysis-fundal height predicts difficult evolution of induced labours. - Indraccolo, Ugo; Nardocci, Lia; Di Iorio, Romolo; Bonito, Marco; Indraccolo, Salvatore Renato (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: Symphysis-fundal-height (SFH) could be prove useful for the management of labour. This study aims to assess the behaviour of induced labours in relationship with SFH values. Methods: Prospective observational study in a sample of 158 women underwent induction with intravaginal dinoprostone for different indications. SFH, SFH corrected for station, gestational age and parity were considered independent variables in multivariable models. Vaginal delivery, operative vaginal delivery, Cesarean section, Cesarean section for dystocia, Cesarean section for cardiotochographyc abnormalities, oxytocin infusion (for potentiating labour), need of Kristeller’s maneuvre, epidural anesthesia (on demand), episiotomy, time from the first dose of dinoprostone to delivery, and time of active phase of labour were considered dependent variables in multivariable models. Results: SFH >34 cm (both uncorrected and corrected for station) independently associates with an increase of odds ratio for operative vaginal birth, Kristeller’s maneuver, oxytocin use, episiotomy. Additionally, SFH >34 cm (corrected for station) seems to correlate with increasing time of active phase of labour. Conclusions: SFH >34 cm (both corrected and uncorrected for station) predicts difficult vaginal deliveries and operative vaginal deliveries in induced labours